1995
DOI: 10.1002/hlca.19950780722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thiophene‐Substituted Spiropyrans and Spirooxazines, Precursors of Photochromic Polymers

Abstract: The synthesis of spiropyrans 11 and 12 and spirooxazines 15-17 containing a thiophene moiety is described. Two different synthetic approaches were used. The spectrokinetic properties of these new compounds are reported.Introduction. - [8]. The modification of the optical, electronic, and electrochemical properties of these materials is the main goal of research efforts. Thus, the synthesis of new precursor structures to prepare new conducting materials remains a current challenge for organic chemists. The typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…16, 70, 77, 155 ± 160 The NMR spectra of spirooxazines are informative and allow one, with rare exception (for example, in the case of SPO 85 and 96), to establish reliably the structures of the resulting compounds. Numerous publications 15,35,40,58,61,106,107,161 and a special-purpose study 162 included the detailed assignments of the signals for protons and carbon atoms in the 1 H and 13 C NMR spectra of a broad spectrum of SPO. It should be noted that an unexpected correlation between the chemical shift of the 2 H -carbon atom of SPO in the 13 C NMR spectra and the positions of the absorption maxima of their coloured forms was found in the study.…”
Section: Structures Of Isomeric Forms Of Spirooxazines and Their Inte...mentioning
confidence: 99%
“…16, 70, 77, 155 ± 160 The NMR spectra of spirooxazines are informative and allow one, with rare exception (for example, in the case of SPO 85 and 96), to establish reliably the structures of the resulting compounds. Numerous publications 15,35,40,58,61,106,107,161 and a special-purpose study 162 included the detailed assignments of the signals for protons and carbon atoms in the 1 H and 13 C NMR spectra of a broad spectrum of SPO. It should be noted that an unexpected correlation between the chemical shift of the 2 H -carbon atom of SPO in the 13 C NMR spectra and the positions of the absorption maxima of their coloured forms was found in the study.…”
Section: Structures Of Isomeric Forms Of Spirooxazines and Their Inte...mentioning
confidence: 99%
“…This concept is at the origin of the recent synthesis of a series of model compounds elaborated by appending oligothiophenic chains to various photochromic 3H-naphtho[2,1-b]pyran molecules derived from the [2H]-chromene family (Chart 1). [6][7][8][9][10][11][12][13][14][15][16][17] Thiophene oligomers were chosen as models of molecular wire because, above two or three thiophene units, their conducting and semiconducting properties are similar to those of very long polythiophene chains. [18][19][20] Naphthopyrans were chosen in regard to their excellent photochromic properties: high colorability, rapid thermal relaxation, and high resistance to fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…This concept is at the origin of the recent synthesis of a series of model compounds elaborated by appending oligothiophenic chains to various photochromic 3H-naphtho[2,1- b ]pyran molecules derived from the [2H]-chromene family (Chart ). Thiophene oligomers were chosen as models of molecular wire because, above two or three thiophene units, their conducting and semiconducting properties are similar to those of very long polythiophene chains. Naphthopyrans were chosen in regard to their excellent photochromic properties: high colorability, rapid thermal relaxation, and high resistance to fatigue. In this family, photochromism proceeds via the cleavage of the geminal diaryl carbon−oxygen single bond (C 3 −O) of the chromene moiety. , The reaction leads to a mixture of colored merocyanine isomers (open forms, OF) with extended π conjugation that might couple electronically substituents in positions 3 and 8 that are uncoupled in the closed form (CF). A molecular photoswitch behavior has been actually demonstrated for a 3H-naphtho[2,1- b ]pyran compound substituted by bithiophenic groups in positions 3 and 8, with the observation of a very strong current density variation upon irradiation. , However it has also been observed that the efficiency of photocolorability of the molecule decreases markedly or even vanishes when the substituted oligothiophenic chains become too long.…”
Section: Introductionmentioning
confidence: 99%
“…In the context, in previous publications, we described the synthesis of spiropyrans, spirooxazines [7], and chromenes [8] containing a thiophene moiety. The introduction of this heterocycle allows subsequent elaboration of polythiophene with photomodulable optoelectronic properties by electrochemical polymerization [9].…”
mentioning
confidence: 99%